Video tutorial for studio lighting subject in blended learning / Mohamad Zaidi Sulaiman - Sulaiman, Mohamad Zaidi (2015)
The use of technology in education has long thrived. Day after day the transformation of education change with time. In line with technological development, educational institution has also developed nicely. The transformation of methods and delivery information are also changed by using additional material that helps instructors disseminate knowledge to students. This research aims to identify the teaching materials that used in Photography education. Studio lighting subject was selected as the research subject. The objective of this research is to produce a video tutorial for studio lighting subject to enhance the student understanding of this subject. The method that been used to collect the data is a Qualitative method. At the first stage, a pilot study was conducted to get the scenario and to investigating the problem. A set of questionnaire was distributed to 03 students in photography department o UiTM Perak. The result shown that over half of 38 respondents not really understand. Another method that used is by Observation in classes. The next stage, a video tutorial was produced after through a video analysis. The element of video tutorial had been studied in progress to produce a good video tutorial. The result has shown that video tutorial gave an impact to the student and makes them more interested to learn.